Determinants of health behavior inequalities: a cross-sectional study from Israel - (:unkn) unknown (OXFORD UNIV PRESS, 2019)
Health behaviors are shaped by the opportunities people have; and the choices they make according to these opportunities. Inequality in economic, cultural and social resources causes disparities in health and health behaviors. Jerusalem has a multiethnic structure, mainly made up of Jews and Arabs. Arabs and Ultra-Orthodox Jews are disadvantaged in terms of socio-economic and health indicators. The purpose of this study is to determine the factors associated with three health behaviors: physical activity (PA), fruit and vegetable consumption, and smoking. This cross-sectional study was conducted among 1682 adults from a stratified sample by age, sex and neighborhood from 2011 to 2015, in accordance with the Healthy Cities project. Univariate analyses were conducted by Chi-square test of independence; and multivariate analyses by logistic regression models. Of the total population, 12% do adequate amounts of PA; 17.6% consume adequate amounts of fruits/vegetables; and 19.4% are current smokers. Multivariate analyses indicates for both genders: ethnicity/religion and education level is associated with doing PA; ethnicity/religion, education and income level is associated with fruit/vegetable consumption; and ethnicity/religion, and age is associated with smoking. However, gender significantly modifies the effect of ethnicity/religion for all the three health behaviors. Gender disparities regarding health behaviors are higher among Arabs and Ultra-Orthodox Jews. In similar economic, cultural and social circumstances, men and women have similar health behaviors; and unequal opportunity to education and income creates a vicious gender inequality cycle. Therefore, to reduce health behavior inequalities, besides economic and cultural inequalities, social and gender inequalities should also be reduced.
Keywords: Israel; health behavior; healthy cities; ethnic; gender; PHYSICAL-ACTIVITY; DIETARY; SMOKING; NUTRITION; INCOME; ARABS; JEWS